Religiusitas Simbolik dan Literasi Fungsional: Studi Persepsi Nasabah Terhadap Produk Tabungan Syariah di Gampong Meureubo - Hidayah, Ainun; Muliza, Muliza; Murlisa, Lia (Universitas Hamzanwadi, 2025)
This study aims to analyze the level of understanding and perceptions of the people of Gampong Meureubo, West Aceh District, regarding the profit-sharing concept in Islamic savings products. Using a descriptive qualitative approach, data were collected through in-depth interviews with seven purposively selected Islamic bank customers. The findings reveal that the community’s understanding of profit-sharing mechanisms remains low to moderate. Customer perceptions are categorized into three groups: positive, neutral, and critical. Internal factors such as educational background, banking experience, and religious motivations, as well as external factors such as bank communication strategies and social community influences, significantly shape customers’ understanding of the profit-sharing system. This study highlights the importance of transparency and community-based education to enhance functional financial literacy, rather than relying solely on symbolic loyalty towards Islamic banking labels. These findings contribute both empirically and theoretically to the development of Islamic financial literacy strategies, especially in regions with formally mandated Islamic financial systems like Aceh